When they met again [large type] - Gould, Leslie, 1962- (Gould, Leslie, 1962- Letters from Lancaster County, 2026)
"It's love at first sight for Adam Slaybaugh, yet while Joanna Grebel finds him attractive and is intrigued when he declares his interest, she's less certain of the potential for a romantic future together. Instead, she proposes they be "just friends," but Adam's not willing to settle for anything less than a romantic relationship. In response, he leaves Lancaster County for Florida, and soon after, Joanna begins courting Jacob Byer--someone she deems a much more suitable match. When Adam returns to Lancaster County years later to pursue a career in his grandparents' successful home renovation business, he finds Joanna suffering from a broken heart. Misunderstandings and matchmaking schemes begin a tender journey of healing and romance--but is Adam's love enough to finally win Joanna over?"--